Confronting Gender in Literature: Male-Female Conflict in Dorothy Parker’s and Kate Chopin’s Short Stories - Chirig, Abdelkrim (International Journal of Language and Literary Studies, 2025)
This article examines the portrayal of male–female conflict in Dorothy Parker’s short story “The Last Tea” (1926) and Kate Chopin’s “The Storm” (1898) and “The Story of an Hour” (1894). Through a comparative literary analysis grounded in feminist theory, the study explores how each narrative depicts power dynamics, gender roles, and the struggle for female autonomy in different historical contexts. Parker’s “The Last Tea” presents a subtle battle of the sexes in which a young woman’s quest for male attention and validation leads to quiet despair, illustrating the imbalance of power and emotional cruelty in modern courtship. In contrast, Chopin’s stories challenge 19th-century gender norms: “The Story of an Hour” depicts a repressed wife’s fleeting freedom from patriarchy, while “The Storm” presents female desire as natural and unpunished. Using close reading and comparative analysis, the article discusses how each author uses irony, symbolism, and narrative perspective to illuminate the conflicts (overt or latent) between men and women. The results show that, despite tonal differences, all three stories highlight women’s limited agency and critique cultural norms shaping male–female relationships, while offering new insights into early feminist themes in American short fiction through a comparison of Parker and Chopin’s works.